Fragility Models for Industrial Equipment Subjected to Natural Hazards - Oreste S. Bursi; Hazif Liaqat Ali; Chiara Nardin; Marco Broccardo; Gianluca Quinci; Fabrizio Paolacci; Luca Caracoglia (Chemical Engineering Transactions)
Large cylindrical storage tanks are widely utilised in petrochemical plants to store different liquid materials, e.g., crude oil. However, these structures are revealed to be especially vulnerable in case of a natural event like an earthquake or tsunami. Damage to these tanks, indeed, can lead to technology accidents (also known as NaTech), like a spill of dangerous materials or waste of filling, typically through failed sealings. To address the challenges of leakage modelling, fragility models associated to leakage due to seismic loading conditions of large cylindrical storage tanks, specifically a broad tank endowed with a single-deck floating roof, are studied. In particular, this paper aims to utilise a probabilistic model to evaluate fragility curves associated with leakage due to slosh-induced damage of single-deck floating roofs and/or seals of broad tanks. The assessment of failure mechanisms and leakage of pantograph-type mechanical seals is considered by means of local FE models. In addition, refined FE models of broad tanks with floating roofs are considered too. Specifically, a broad tank TK-59 endowed with an 86 m diameter and a 22 m height storing crude oil was selected and investigated as an industrial case study. Finally, fragility functions are derived and commented upon for the most relevant limit states associated with leakage.